2001
DOI: 10.1002/cncr.10146
|View full text |Cite
|
Sign up to set email alerts
|

Lack of significant differences in the corrected activity of lysophospholipase D, producer of phospholipid mediator lysophosphatidic acid, in incubated serum from women with and without ovarian tumors

Abstract: BACKGROUND Several studies have shown that lysophosphatidic acid (LPA), a phospholipidic chemical mediator, is relevant to the pathogenesis of ovarian carcinoma. Higher plasma levels of LPA have been reported in patients with ovarian carcinoma than in healthy patients, and LPA is known to activate ovarian carcinoma cells. To determine the reason for the increased plasma LPA levels in ovarian carcinoma patients, we compared the activities of serum lysophospholipase D, a novel LPA‐producing metallo‐enzyme, in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…High levels of lysophosphatidic acid, a product of lysophospholipase catalytic activity, have been reported as a potential biomarker of ovarian cancer (33). However, lysophospholipase activity levels in serum do not seem to be associated with ovarian carcinoma (34). To our knowledge, GNAI2, GPX1, and CCT3 are not known to be overexpressed in ovarian cancer and may be entirely novel markers for this disease.…”
Section: Discussionmentioning
confidence: 81%
“…High levels of lysophosphatidic acid, a product of lysophospholipase catalytic activity, have been reported as a potential biomarker of ovarian cancer (33). However, lysophospholipase activity levels in serum do not seem to be associated with ovarian carcinoma (34). To our knowledge, GNAI2, GPX1, and CCT3 are not known to be overexpressed in ovarian cancer and may be entirely novel markers for this disease.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, a recent report showing that the activity of serum lysoPLD in patients with ovarian cancer was almost the same as those in healthy subjects and patients with a benign ovarian tumor (Table I) [Tokumura et al, 2002b]. Previous results showing a similar elevated serum level of LPA in patients with multiple myeloma [Sasagawa et al, 1999] may indicate that increase in the LPA level in the blood circulation is not a good selective marker of ovarian cancer.…”
Section: Lpamentioning
confidence: 83%
“…extracellular conversion from other lysophospholipids. In the latter pathway, ATX/lysoPLD is shown to be a key enzyme in the production of LPA by the catalysis of LPC, which is known to be abundantly present in plasma and tissue fluids [3,64,66]. In this study, we found a subtype of MC in the human gastrointestinal tract that showed strong staining for ATX/lysoPLD.…”
Section: Discussionmentioning
confidence: 68%